Meta-aramid nano pulp as well as preparation method and application thereof
Through the preparation of meta-aramid spinning raw liquid and electrospinning technology, combined with hot pressing and water washing processes, meta-aramid nanopulp with high specific surface area is prepared, which solves the complex process and high solvent recovery cost in the existing technology. The problem of this paper has achieved efficient and low-cost meta-aramid nanopulp production, improving product performance.
Patent Information
- Application Number
- CN202411416839.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The existing meta-aramid pulp preparation technology has complex process flow, high solvent recovery cost and low specific surface area of the product, resulting in high production costs.
The preparation of meta-aramid spinning stock solution, nano-non-woven fabrics, nano-slicing preparation and nano-pulp preparation methods are adopted, and the solvent recovery system is combined with the process of electrospinning, hot pressing, water washing and drying. Meta-aramid nanopulp with high specific surface area was prepared.
The process flow is simplified, investment costs are reduced, the specific surface area and dispersion of the product are improved, the strength and tearing properties of aramid paper and composite materials are significantly improved, and the solvent recovery cost is reduced.
Smart Images

Figure CN119287550A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of synthetic fibers and relates to meta-aramid nano pulp and a preparation method and application thereof. Background Art
[0002] Meta-aramid, also known as MPIA (Poly-m-phenyleneisophthalamide), began to be studied in 1956 and was industrialized in 1967. The macromolecular chain of meta-aramid is zigzag, and it has excellent high temperature resistance, flame retardancy, electrical insulation, radiation resistance, physical and chemical properties. The glass transition temperature of meta-aramid is 270°C, and no obvious decomposition and carbonization will occur below 350°C. When the temperature exceeds 400°C, the fiber gradually becomes brittle, carbonized and decomposed, but no molten droplets are produced; the limiting oxygen index of meta-aramid is 28%, and it does not burn in the flame, and has good flame retardancy; meta-aramid is very stable in acids, alkalis, bleaches, reducing agents and organic solvents.
[0003] Meta-aramid paper can be prepared with meta-aramid chopped fiber and meta-aramid pulp as the main raw materials. Meta-aramid paper has high temperature resistance, good insulation, excellent mechanical strength and electrical properties, and has been successfully used in electrical equipment such as motors, transformers, capacitors, etc. Transformers are the field where aramid insulation paper is used the most. At present, meta-aramid paper series transformers have been successfully used in national key projects such as the Shenzhou V manned space project and the Three Gorges Project on the Yangtze River. Honeycomb core structural materials made of aramid paper have the characteristics of light weight, impact resistance, high strength, and aging resistance. They are mainly used in aircraft, missiles, satellite broadband wave-transparent materials, and high-rigidity secondary load-bearing structural components (wings, flow cover cabin linings, aircraft doors, floors, cargo holds and partitions), and the market prospects are very broad.
[0004] With the continuous development of meta-aramid paper applications, the requirements for meta-aramid pulp preparation technology are becoming increasingly higher. At present, the preparation technology for meta-aramid pulp is the traditional precipitation method. The meta-aramid pulp prepared by this method is also called meta-aramid precipitated fiber, with a specific surface area of 30 to 50 m 2 / g, and several companies and institutions have successively studied similar fiber precipitation technology. For example, CN104630924A discloses a method for preparing an aromatic polyamide film-like fiber precipitation, which dilutes the meta-aramid polymer stock solution, uses water, DMAC and chloride salt mixture as a precipitating agent, and obtains meta-aramid fiber precipitation through precipitation, filtration and water washing. US3018091A discloses the structure of a precipitation device, which mentions the preparation process of fiber precipitation using water and DMF as precipitation solvents. US3756908A discloses a preparation technology for aromatic polyamide paper, and the fiber precipitation used in making paper also adopts the process technology in US3018091A. However, the meta-aramid pulp obtained by precipitation method has a low specific surface area, resulting in a low cohesion between fibers during papermaking, and the concentration of the solvent to be recovered is too low (30% to 50%), resulting in a high production cost.
[0005] Therefore, in the art, it is desired to develop a method for preparing meta-aramid pulp, wherein the meta-aramid pulp obtained by the method has a high specific surface area, a high concentration of solvent to be recovered, and a low production cost. Summary of the invention
[0006] The purpose of the present invention is to solve the problems in the prior art of meta-aramid pulp production, such as complex process flow, high solvent recovery cost, low specific surface area of the product, etc. The present invention provides a method for preparing meta-aramid nano pulp, which can effectively solve the above problems, and has a simple process flow and is easy to operate and control.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing meta-aramid nano pulp, the preparation method comprising:
[0009] (1) Preparation of meta-aramid spinning solution: mixing a poly(m-phenylene isophthalamide) solution and an amine solvent, and stirring to obtain a meta-aramid spinning solution;
[0010] (2) Preparation of meta-aramid nano nonwoven fabric: The meta-aramid spinning stock solution obtained in step (1) is transported to an electrospinning machine to prepare a meta-aramid nano nonwoven fabric; during the preparation of the meta-aramid nano nonwoven fabric, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into liquid, and then the liquid solvent is sent to a solvent recovery system;
[0011] (3) Preparation of meta-aramid nano-slices: The meta-aramid nano-nonwoven fabric obtained in step (2) is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the shaped meta-aramid nano-nonwoven fabric is then cut into meta-aramid nano-slices; during the hot pressing process, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into liquid, and then the liquid solvent is sent to a solvent recovery system; the washing water after washing is sent to a water treatment facility for processing and then reused;
[0012] (4) Preparation of meta-aramid nano pulp: The meta-aramid nano slices obtained in step (3) are pulped, refined, and filtered to obtain the meta-aramid nano pulp; the filtrate after filtration is used as washing water in the washing section.
[0013] The preparation method of meta-aramid nano pulp provided by the present invention has a simple process flow and lower investment cost than the traditional precipitation method. By adjusting the process parameters, a series of nano-scale meta-aramid pulps with high specific surface area and stable performance and size can be obtained. The pulps can be applied to the fields of aramid paper and high-performance reinforced composite materials, and can significantly improve the strength and tearing properties of aramid paper and composite materials.
[0014] Preferably, the solvent in the poly(m-phenylene isophthalamide) solution and the amine solvent added later are the same solvent.
[0015] Preferably, the concentration of the poly(m-phenylene isophthalamide) solution is 20% to 25%, for example, 20%, 21%, 22%, 23%, 24%, 25%, etc.
[0016] Preferably, the intrinsic viscosity of the poly(m-phenylene isophthalamide) is 1.2 to 1.9 dL / g, for example, 1.2 dL / g, 1.3 dL / g, 1.4 dL / g, 1.5 dL / g, 1.6 dL / g, 1.7 dL / g, 1.8 dL / g, 1.9 dL / g, etc.
[0017] In the present invention, the intrinsic viscosity (the reduced viscosity when the concentration of the polymer solution approaches zero) is obtained by referring to GB / T3401-2007 test.
[0018] The amine solvent in step (1) includes any one of N,N-dimethylacetamide, N-methylpyrrolidone or N-acetylpyrrolidone.
[0019] Preferably, the water content of the amine solvent is lower than 120 ppm, for example, 110 ppm, 100 ppm, 80 ppm, 60 ppm, 50 ppm, etc.
[0020] Preferably, the solid content of the meta-aramid spinning solution in step (1) is 8% to 18%, for example, 8%, 9%, 10%, 12%, 14%, 16%, 18%, etc., and its temperature is controlled to be 10 to 50°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, etc.
[0021] Preferably, the mixing in step (1) is carried out under the protection of dry inert gas.
[0022] Preferably, the inert gas comprises nitrogen.
[0023] Preferably, the conditions for the electrospinning in step (2) include: a voltage of 10 to 40 kV, such as 10 kV, 15 kV, 20 kV, 25 kV, 30 kV, 35 kV, 40 kV, etc., a relative humidity of 40% to 60%, such as 40%, 45%, 50%, 55%, 60%, etc., a distance from the Taylor cone to the meta-aramid nano nonwoven fabric receiving device of 5 to 30 cm, such as 5 cm, 10 cm, 15 cm, 20 cm, 25 cm, 30 cm, etc., a spinning solution flow rate of 0.2 to 1 mL / h, such as 0.2 mL / h, 0.4 mL / h, 0.6 mL / h, 0.8 mL / h, 1 mL / h, etc., and a hot air temperature of 40 to 80 ° C, such as 40 ° C, 45 ° C, 50 ° C, 55 ° C, 60 ° C, 65 ° C, 70 ° C, 75 ° C, etc.
[0024] In the meta-aramid nano nonwoven fabric prepared in step (2), the fiber diameter is 10 to 100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0025] The meta-aramid nano nonwoven fabric prepared in step (2) has an average thickness of 100 to 1000 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, etc., a porosity of 50% to 90%, for example, 50%, 60%, 70%, 80%, 90%, etc., a tensile strength of 0.05 to 0.9 MPa, for example, 0.05 MPa, 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, etc., and an elastic elongation of 4% to 18%, for example, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, etc.
[0026] Preferably, the conditions for hot pressing in step (3) are as follows: the surface temperature of the hot pressing roller is 70-100°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.; the working line pressure of the hot pressing is 1-50 kn / m, for example, 1 kn / m, 3 kn / m, 5 kn / m, 8 kn / m, 10 kn / m, 15 kn / m, 20 kn / m, 25 kn / m, 30 kn / m, 35 kn / m, 40 kn / m, 45 kn / m, 50 kn / m, etc.; the temperature of the hot air during the hot pressing process is 75-105°C, for example, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, etc.
[0027] Preferably, the drying conditions in step (3) are as follows: the surface temperature of the drying roller is 150-190°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, etc.
[0028] Preferably, the meta-aramid nano-slices in step (3) are square pieces with a side length of 4 to 10 mm, such as 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, etc.
[0029] Preferably, the concentration of the liquid solvent to be recovered in step (2) and step (3) is both above 90% (eg, 90%, 92%, 94%, 96%, 98%, etc.).
[0030] Preferably, desalted water is added during the slurry preparation in step (4).
[0031] Preferably, the conductivity of the desalted water is <9 μs / cm (e.g., 8 μs / cm, 6 μs / cm, 5 μs / cm, etc.), total Fe ≤ 50 μg / L (e.g., 50 μg / L, 45 μg / L, 40 μg / L, etc.), hardness (in terms of CaCO3) ≤ 2 μmmol / L (e.g., 2 μmmol / L, 1 μmmol / L, etc.), and pH value is 7-8 (e.g., 7, 7.5, 8, etc.).
[0032] Preferably, the concentration of the slurry in step (4) is 1% to 5%, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.
[0033] Preferably, the pulp inlet pressure during the pulping process in step (4) is 0.15-0.3 MPa, for example, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa, etc.
[0034] Preferably, the moisture content of the meta-aramid nano-pulp in step (4) is 85% to 95%, for example, 85%, 86%, 88%, 90%, 92%, 93%, 95%, etc.
[0035] Preferably, the specific surface area of the meta-aramid nano pulp in step (4) is 60 to 80 m 2 / g, for example 60m 2 / g, 62m 2 / g, 64m 2 / g, 66m 2 / g, 68m 2 / g, 70m 2 / g, 72m 2 / g, 74m 2 / g, 76m 2 / g, 78m 2 / g, 80m 2 / g, etc., the length is 2 to 5 mm, such as 2 mm, 3 mm, 4 mm, 5 mm, etc., and the density is 1.33 to 1.36 g / cm 3 , for example 1.33 g / cm 3 , 1.34g / cm 3 , 1.35g / cm 3 , 1.36g / cm 3 The solvent content is less than 0.01%, such as 0.008%, 0.006%, 0.005%, etc., which can meet the market demand for the product.
[0036] As a preferred technical solution of the present invention, the preparation method comprises:
[0037] (1) Preparation of meta-aramid spinning stock solution: Under the protection of dry inert gas, firstly, a poly(m-phenylene isophthalamide) solution with a concentration of 20% to 25% is added to a stock solution preparation tank, and then an amine solvent is added and stirred to obtain a meta-aramid spinning stock solution with a solid content of 8% to 18%; then, the meta-aramid spinning stock solution is cooled to 10 to 50° C.;
[0038] (2) Preparation of meta-aramid nano nonwoven fabric: The meta-aramid spinning stock solution obtained in step (1) is conveyed to an electrospinning machine to obtain a meta-aramid nano nonwoven fabric having a fiber diameter of 10 to 100 nm, an average thickness of 100 to 1000 nm, a porosity of 50% to 90%, a tensile strength of 0.05 to 0.9 MPa, and an elastic elongation of 4% to 18%. During the preparation of the meta-aramid nano nonwoven fabric, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into a liquid, and then the liquid solvent is sent to a solvent recovery system;
[0039] The conditions for electrospinning include: a voltage of 10 to 40 kV, a relative humidity of 40% to 60%, a distance from the Taylor cone to the receiving device for the meta-aramid nano nonwoven fabric of 5 to 30 cm, a spinning solution flow rate of 0.2 to 1 mL / h, and a hot air temperature of 40 to 80°C;
[0040] (3) Preparation of meta-aramid nano-slices: The meta-aramid nano-nonwoven fabric obtained in step (2) is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the conditions for hot pressing and drying are: the surface temperature of the hot pressing roller is 70-100°C, the working line pressure of the hot pressing is 1-50 kn / m, the temperature of the hot air during the hot pressing process is 75-105°C, and the surface temperature of the drying roller is 150-190°C; the shaped meta-aramid nano-nonwoven fabric is then cut into square meta-aramid nano-slices with a side length of 4-10 mm by a slicer; during the hot pressing process, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into liquid, and then the liquid solvent is sent to a solvent recovery system; the washing water after washing is sent to a water treatment facility for processing and then reused;
[0041] (4) Preparation of meta-aramid nano pulp: desalted water is added to the meta-aramid nano slices obtained in step (3) to prepare a slurry with a concentration of 1% to 5%, and then the slurry is subjected to the steps of refining, filtering and packaging to obtain the meta-aramid nano pulp suitable for aramid paper manufacturing and other fields; the filtrate after filtration is used as washing water in the washing section.
[0042] In a second aspect, the present invention provides a meta-aramid nano-pulp, which is prepared by the preparation method described in the first aspect.
[0043] In a third aspect, the present invention provides a use of the meta-aramid nano pulp as described in the second aspect in aramid paper or reinforced composite materials.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The preparation method of the meta-aramid nano-pulp provided by the present invention has a much higher concentration (90%) of the solvent to be recovered than that (30% to 50%) of the solvent to be recovered by the precipitation method, so the solvent recovery cost is much lower than that of the precipitation method; the specific surface area (60 to 80 m 2 / g) is much higher than the specific surface area of precipitated fibers (30-50m 2 / g), the prepared meta-aramid nano pulp has good dispersibility, fine and rich morphology and hairiness, and the process is simple and effective. The meta-aramid nano nonwoven fabric slices manufactured by the present invention are nano-scale products, and meta-aramid nano pulp can be obtained by a little refining, and the processing cost is lower than the refining cost of precipitated fibers. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The present invention provides a flow chart of a method for preparing meta-aramid nano-pulp according to an embodiment of the present invention. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] Example 1
[0049] In this embodiment, a method for preparing meta-aramid nano pulp is provided, such as Figure 1 As shown, the preparation method comprises the following steps:
[0050] (1) Preparation of meta-aramid spinning stock solution: Under the protection of dry nitrogen, firstly, a 20% poly(m-phenylene isophthalamide) solution (the intrinsic viscosity of poly(m-phenylene isophthalamide) is 1.3 dL / g) is added into a stock solution preparation tank, and then an appropriate amount of N,N-dimethylacetamide (DMAC) is added in proportion and stirred evenly to obtain a meta-aramid spinning stock solution with a solid content of 17%; then, the meta-aramid spinning stock solution is cooled to 20° C. and set aside;
[0051] (2) Preparation of meta-aramid nano nonwoven fabric: Under the high-voltage electrospinning conditions of: voltage 10 kV, relative humidity 50%, distance from Taylor cone to nanofiber nonwoven fabric receiving device 20 cm, spinning solution flow rate 0.3 mL / h, hot air temperature 60°C, the prepared meta-aramid spinning solution was transported into a high-voltage electrospinning machine to obtain a meta-aramid nanofiber nonwoven fabric with a fiber diameter of 55 nm, an average nonwoven fabric thickness of 320 nm, a porosity of 88%, a tensile strength of 0.22 MPa, and an elastic elongation of 12%; during the preparation of the nonwoven fabric, dry hot air was introduced to send the volatilized amine solvent into a heat exchanger to condense it into a liquid, and then the liquid solvent was sent to a solvent recovery system (the concentration of the liquid solvent to be recovered was 94.6%);
[0052] (3) Preparation of meta-aramid nano-slices: The prepared meta-aramid nano-nonwoven fabric is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the conditions for hot pressing and drying are: the surface temperature of the hot pressing roller is 75°C, the working line pressure of the hot pressing is 6kn / m, the temperature of the hot air during the hot pressing process is 80°C, and the surface temperature of the drying roller is 152°C; the shaped meta-aramid nano-nonwoven fabric is cut into square meta-aramid nano-slices using a slicer, and the slice specification is 5mm in side length; dry hot air is introduced during the hot pressing process, and the volatilized amine solvent is sent to a heat exchanger to condense into liquid, and then the liquid solvent is sent to a solvent recovery system (the concentration of the liquid solvent to be recovered is 93.7%); the washing water after washing is sent to a water treatment facility for processing and then reused;
[0053] (4) Preparation of meta-aramid nano-pulp: Add an appropriate amount of desalted water to the meta-aramid nano-chips to prepare a slurry with a concentration of 1.5%, and then go through the processes of refining (the pulp inlet pressure is 0.16 MPa), filtering and packaging to obtain meta-aramid nano-pulp with a moisture content of 90%. The filtrate after filtration is used as washing water in the washing section.
[0054] The obtained meta-aramid nano pulp is in the form of fine white translucent fibers or films, with an average specific surface area of 78 m 2 / g, the average fiber length is 2.8mm, and the density of meta-aramid nano pulp is 1.34g / cm 3 , the solvent content is 0.004%.
[0055] Example 2
[0056] In this embodiment, a method for preparing meta-aramid nano pulp is provided, such as Figure 1 As shown, the preparation method comprises the following steps:
[0057] (1) Preparation of meta-aramid spinning stock solution: Under the protection of dry nitrogen, firstly, a 20% poly(m-phenylene isophthalamide) solution (the intrinsic viscosity of poly(m-phenylene isophthalamide) is 1.5 dL / g) is added into a stock solution preparation tank, and then an appropriate amount of N,N-dimethylacetamide (DMAC) is added in proportion and stirred evenly to obtain a meta-aramid spinning stock solution with a solid content of 15%; then, the meta-aramid spinning stock solution is cooled to 25° C. and set aside;
[0058] (2) Preparation of meta-aramid nano nonwoven fabric: Under the high-voltage electrospinning conditions of: voltage 10 kV, relative humidity 50%, distance from Taylor cone to nanofiber nonwoven fabric receiving device 20 cm, spinning solution flow rate 0.5 mL / h, hot air temperature 65°C, the prepared meta-aramid spinning solution was transported into a high-voltage electrospinning machine to obtain a meta-aramid nanofiber nonwoven fabric with a fiber diameter of 67 nm, an average nonwoven fabric thickness of 420 nm, a porosity of 81%, a tensile strength of 0.28 MPa, and an elastic elongation of 10%; during the preparation of the nonwoven fabric, dry hot air was introduced to send the volatilized amine solvent into a heat exchanger to condense it into a liquid, and then the liquid solvent was sent to a solvent recovery system (the concentration of the liquid solvent to be recovered was 95.1%);
[0059] (3) Preparation of meta-aramid nano-slices: The prepared meta-aramid nano-nonwoven fabric is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the conditions for hot pressing and drying are: the surface temperature of the hot pressing roller is 80°C, the working line pressure of the hot pressing is 6kn / m, the temperature of the hot air during the hot pressing process is 85°C, and the surface temperature of the drying roller is 161°C; a slicer is used to cut the shaped meta-aramid nano-nonwoven fabric into square meta-aramid nano-slices, and the slice specification is 5mm in side length; dry hot air is introduced during the hot pressing process, and the volatilized amine solvent is sent to a heat exchanger to condense into liquid, and then the liquid solvent is sent to a solvent recovery system (the concentration of the liquid solvent to be recovered is 93.4%); the washing water after washing is sent to a water treatment facility for processing and then reused;
[0060] (4) Preparation of meta-aramid nano-pulp: Add an appropriate amount of desalted water to the meta-aramid nano-chips to prepare a slurry with a concentration of 2%, and then go through the processes of refining (the pulp inlet pressure is 0.16 MPa), filtering and packaging to obtain meta-aramid nano-pulp with a moisture content of 90%. The filtrate after filtration is used as washing water in the washing section.
[0061] The obtained meta-aramid nano pulp is in the form of fine white translucent fibers or films, with an average specific surface area of 72 m 2 / g, the average fiber length is 2.5mm, and the density of meta-aramid nano pulp is 1.35g / cm 3 , the solvent content is 0.005%.
[0062] Example 3
[0063] In this embodiment, a method for preparing meta-aramid nano pulp is provided, such as Figure 1 As shown, the preparation method comprises the following steps:
[0064] (1) Preparation of meta-aramid spinning stock solution: Under the protection of dry nitrogen, firstly, a 20% poly(m-phenylene isophthalamide) solution (the intrinsic viscosity of poly(m-phenylene isophthalamide) is 1.7 dL / g) is added into a stock solution preparation tank, and then an appropriate amount of N,N-dimethylacetamide (DMAC) is added in proportion and stirred evenly to obtain a meta-aramid spinning stock solution with a solid content of 12%; then, the meta-aramid spinning stock solution is cooled to 28° C. and set aside;
[0065] (2) Preparation of meta-aramid nano nonwoven fabric: Under the high-voltage electrospinning conditions of: voltage 10 kV, relative humidity 50%, distance from Taylor cone to nanofiber nonwoven fabric receiving device 20 cm, spinning solution flow rate 0.7 mL / h, hot air temperature 70°C, the prepared meta-aramid spinning solution was transported into a high-voltage electrospinning machine to obtain a meta-aramid nanofiber nonwoven fabric with a fiber diameter of 73 nm, an average nonwoven fabric thickness of 590 nm, a porosity of 77%, a tensile strength of 0.33 MPa, and an elastic elongation of 9%; during the preparation of the nonwoven fabric, dry hot air was introduced to send the volatilized amine solvent into a heat exchanger to condense it into a liquid, and then the liquid solvent was sent to a solvent recovery system (the concentration of the liquid solvent to be recovered was 94.8%);
[0066] (3) Preparation of meta-aramid nano-slices: The prepared meta-aramid nano-nonwoven fabric is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the conditions for hot pressing and drying are: the surface temperature of the hot pressing roller is 85°C, the working line pressure of the hot pressing is 6kn / m, the temperature of the hot air during the hot pressing process is 90°C, and the surface temperature of the drying roller is 172°C; the shaped meta-aramid nano-nonwoven fabric is cut into square meta-aramid nano-slices using a slicer, and the slice specification is 5mm in side length; dry hot air is introduced during the hot pressing process, and the volatilized amine solvent is sent to a heat exchanger to condense into liquid, and then the liquid solvent is sent to a solvent recovery system (the concentration of the liquid solvent to be recovered is 93.2%); the washing water after washing is sent to a water treatment facility for processing and then reused;
[0067] (4) Preparation of meta-aramid nano-pulp: An appropriate amount of desalted water is added to the meta-aramid nano-chips to prepare a slurry with a concentration of 2.5%. The slurry is then subjected to processes such as refining (the slurry inlet pressure is 0.16 MPa), filtration and packaging to obtain meta-aramid nano-pulp with a moisture content of 91%. The filtrate after filtration is used as washing water in the washing section.
[0068] The obtained meta-aramid nano pulp is in the form of fine white translucent fibers or films, with an average specific surface area of 68 m 2 / g, the average fiber length is 2.6mm, and the density of meta-aramid nano pulp is 1.35g / cm 3 , the solvent content is 0.006%.
[0069] Example 4
[0070] In this embodiment, a method for preparing meta-aramid nano pulp is provided, such as Figure 1 As shown, the preparation method comprises the following steps:
[0071] (1) Preparation of meta-aramid spinning stock solution: Under the protection of dry nitrogen, firstly, a 20% poly(m-phenylene isophthalamide) solution (the intrinsic viscosity of poly(m-phenylene isophthalamide) is 1.9 dL / g) is added into a stock solution preparation tank, and then an appropriate amount of N,N-dimethylacetamide (DMAC) is added in proportion and stirred evenly to obtain a meta-aramid spinning stock solution with a solid content of 9%; then, the meta-aramid spinning stock solution is cooled to 35° C. and set aside;
[0072] (2) Preparation of meta-aramid nano nonwoven fabric: Under the high-voltage electrospinning conditions of: voltage 10 kV, relative humidity 50%, distance from Taylor cone to nanofiber nonwoven fabric receiving device 20 cm, spinning solution flow rate 0.9 mL / h, hot air temperature 75°C, the prepared meta-aramid spinning solution was transported into a high-voltage electrospinning machine to obtain a meta-aramid nanofiber nonwoven fabric with a fiber diameter of 85 nm, an average nonwoven fabric thickness of 631 nm, a porosity of 71%, a tensile strength of 0.49 MPa, and an elastic elongation of 6%; during the preparation of the nonwoven fabric, dry hot air was introduced to send the volatilized amine solvent into a heat exchanger to condense it into a liquid, and then the liquid solvent was sent to a solvent recovery system (the concentration of the liquid solvent to be recovered was 95.3%);
[0073] (3) Preparation of meta-aramid nano-slices: The prepared meta-aramid nano-nonwoven fabric is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the conditions for hot pressing and drying are: the surface temperature of the hot pressing roller is 90°C, the working line pressure of the hot pressing is 6kn / m, the temperature of the hot air during the hot pressing process is 95°C, and the surface temperature of the drying roller is 181°C; the shaped meta-aramid nano-nonwoven fabric is cut into square meta-aramid nano-slices using a slicer, and the slice specification is 5mm in side length; dry hot air is introduced during the hot pressing process, and the volatilized amine solvent is sent to a heat exchanger to condense into liquid, and then the liquid solvent is sent to a solvent recovery system (the concentration of the liquid solvent to be recovered is 93.6%); the washing water after washing is sent to a water treatment facility for processing and then reused;
[0074] (4) Preparation of meta-aramid nano-pulp: An appropriate amount of desalted water is added to the meta-aramid nano-chips to prepare a slurry with a concentration of 3%, and then the slurry is subjected to the processes of refining (the slurry inlet pressure is 0.16 MPa), filtering and packaging to obtain meta-aramid nano-pulp with a moisture content of 90.5%. The filtrate after filtration is used as washing water in the washing section.
[0075] The obtained meta-aramid nano pulp is in the form of fine white translucent fibers or films, with an average specific surface area of 63 m 2 / g, the average fiber length is 2.3mm, and the density of meta-aramid nano pulp is 1.36g / cm 3 , the solvent content is 0.008%.
[0076] Comparative Example 1
[0077] In this comparative example, a method for preparing meta-aramid nano pulp is provided. The difference between the preparation method and Example 4 is that in step (1), the solid content of the meta-aramid spinning solution is adjusted to 6%. Other materials, amounts, and preparation methods are the same as those in Example 4.
[0078] However, when the experiment reached step (2), the obtained fibers could not be formed because the solid content of the original solution was too low, so the solvent in the fibers could not be completely precipitated, and the non-woven fabric could not be formed in time. Therefore, the relevant parameters of the non-woven fabric (fiber diameter, average thickness of the non-woven fabric, porosity, tensile strength, elastic elongation) could not be detected, resulting in the inability to proceed to steps (3) and (4) of the experiment.
[0079] This experiment has no product output.
[0080] Comparative Example 2
[0081] In this comparative example, a method for preparing meta-aramid nano pulp is provided. The difference between the preparation method and Example 1 is that in step (1), the solid content of the meta-aramid spinning solution is adjusted to 20%. Other materials, amounts, and preparation methods are the same as those in Example 1.
[0082] However, when the experiment reached step (2), the spinneret could not continuously and stably spray out the spinning solution. The reason was that the solid content of the spinning solution was too high, resulting in too high viscosity. The high viscosity caused the friction of the solution flow to be too large, and the solution could not be sprayed out continuously and smoothly, resulting in the inability to proceed to steps (3) and (4).
[0083] This experiment has no product output.
[0084] Comparative Example 3
[0085] In this comparative example, a method for preparing meta-aramid nano pulp is provided. The difference between the preparation method and Example 1 is that the temperature of the hot air is adjusted to 35° C. in step (2). Other materials, amounts and preparation methods are the same as those in Example 1.
[0086] However, when the experiment reached step (2), the obtained fibers could not be formed because the hot air temperature was too low, so the solvent in the fibers could not be completely precipitated, and the nonwoven fabric could not be formed in time. Therefore, the relevant parameters of the nonwoven fabric (fiber diameter, average thickness of the nonwoven fabric, porosity, tensile strength, elastic elongation) could not be detected, resulting in the inability to proceed to steps (3) and (4) of the experiment.
[0087] This experiment has no product output.
[0088] Comparative Example 4
[0089] In this comparative example, a method for preparing meta-aramid nano-pulp is provided. The difference between the preparation method and Example 4 is that the temperature of the hot air is adjusted to 90° C. in step (2). Other materials, amounts and preparation methods are the same as those in Example 1.
[0090] However, when the experiment proceeded to step (2), an meta-aramid nanofiber nonwoven fabric with a fiber diameter of 85 nm, an average nonwoven fabric thickness of 635 nm, a porosity of 72%, a tensile strength of 0.53 MPa, and an elastic elongation of 8% was obtained; when the experiment proceeded to step (3), the nonwoven fabric could not be bonded at the intersection of the fibers after hot pressing because the hot air temperature was too high, causing the solvent on the fiber surface to precipitate too quickly, and the fibers were fully formed during hot pressing; after the nonwoven fabric was cut into slices, the slices were loose and not formed, resulting in the inability to proceed to step (4) of the experiment.
[0091] This experiment has no product output.
[0092] By comparing Examples 1 and 4 with Comparative Examples 1 and 2, it can be seen that the present invention obtains a pulp product with better effect by limiting the solid content of the meta-aramid spinning solution. When the solid content of the meta-aramid polymer solution is too low, the solid content of the solution is too low, so that the solvent in the fiber cannot be completely precipitated, and the non-woven fabric cannot be formed in time, resulting in unsustainable production; when the solid content of the meta-aramid polymer solution is too high, the excessively high solid content causes the viscosity of the solution to be too high, and the excessively high viscosity causes the friction of the solution to flow to be too large, and the solution cannot be continuously and smoothly sprayed, which also causes unsustainable production.
[0093] By comparing Examples 1 and 4 with Comparative Examples 3 and 4, it can be seen that the present invention obtains a pulp product with better effect by limiting the hot air temperature during spinning. When the hot air temperature during spinning is too low, the solvent in the fiber cannot be completely precipitated, and the non-woven fabric cannot be formed in time, resulting in unsustainable production; when the hot air temperature during spinning is too high, the excessively high hot air temperature causes the solvent on the fiber surface to precipitate too quickly, and the fiber is completely formed during hot pressing, resulting in the inability to bond the fiber intersections. After the non-woven fabric is cut into slices, the slices are not formed due to the loose internal fibers, which also results in unsustainable production.
[0094] The performance testing method of the meta-aramid nano nonwoven fabric involved in the above embodiments and comparative examples is as follows:
[0095] (1) Porosity: measured by mercury intrusion porosimetry according to GB / T 21650.1-2008;
[0096] (2) Tensile strength: obtained by referring to GB / T12914-2018_constant rate tensile method test;
[0097] (3) Elastic elongation: obtained by referring to GB / T12914-2018_constant rate tensile method test.
[0098] The performance testing method of the meta-aramid nano pulp involved in the above embodiments and comparative examples is as follows:
[0099] (1) Average specific surface area of fiber: obtained by referring to GB / T 19587-2017 test;
[0100] (2) Average fiber length: obtained by referring to TAPPI T271 test.
[0101] In summary, the preparation method of the meta-aramid nano-pulp provided by the present invention has a much higher concentration of the solvent to be recovered (more than 90%) than the concentration of the solvent to be recovered by the precipitation method (30% to 50%), so the solvent recovery cost ratio is much lower than that of the precipitation method; the specific surface area of the prepared meta-aramid nano-pulp (60 to 80 m 2 / g) is much higher than the specific surface area of precipitated fibers (30-50m 2 / g), the meta-aramid nano pulp produced has good dispersibility, fine and rich morphology and hairiness, and simple and effective process. The present invention can produce various products with stable dimensions by adjusting the concentration and temperature of the meta-aramid spinning stock solution, high-voltage electrospinning conditions, slicing conditions, pulping and refining conditions and other parameters. The meta-aramid nano nonwoven fabric slices produced by the present invention are nano-scale products, and the meta-aramid nano pulp can be obtained by a little refining, and the processing cost is lower than the refining cost of precipitated fibers.
[0102] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the meta-aramid nano pulp and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing meta-aramid nano pulp, characterized in that: The preparation method comprises: (1) Preparation of meta-aramid spinning solution: mixing a poly(m-phenylene isophthalamide) solution and an amine solvent, and stirring to obtain a meta-aramid spinning solution; (2) Preparation of meta-aramid nano nonwoven fabric: The meta-aramid spinning stock solution obtained in step (1) is transported to an electrospinning machine to prepare a meta-aramid nano nonwoven fabric; during the preparation of the meta-aramid nano nonwoven fabric, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into liquid, and then the liquid solvent is sent to a solvent recovery system; (3) Preparation of meta-aramid nano-slices: The meta-aramid nano-nonwoven fabric obtained in step (2) is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the shaped meta-aramid nano-nonwoven fabric is then cut into meta-aramid nano-slices; during the hot pressing process, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into liquid, and then the liquid solvent is sent to a solvent recovery system; the washing water after washing is sent to a water treatment facility for processing and then reused; (4) Preparation of meta-aramid nano pulp: The meta-aramid nano slices obtained in step (3) are pulped, refined, and filtered to obtain the meta-aramid nano pulp; the filtrate after filtration is used as washing water in the washing section.
2. The preparation method according to claim 1, characterized in that: The solvent in the poly(m-phenylene isophthalamide) solution and the amine solvent added later are the same solvent; Preferably, the concentration of the poly(m-phenylene isophthalamide) solution is 20% to 25%; Preferably, the intrinsic viscosity of the poly(meta-phenylene isophthalamide) is 1.2 to 1.9 dL / g.
3. The preparation method according to claim 1 or 2, characterized in that: The amine solvent in step (1) includes any one of N,N-dimethylacetamide, N-methylpyrrolidone or N-acetylpyrrolidone; Preferably, the water content of the amine solvent is lower than 120 ppm.
4. The preparation method according to any one of claims 1 to 3, characterized in that The solid content of the meta-aramid spinning solution in step (1) is 8% to 18%, and the temperature thereof is controlled to be 10 to 50° C.; Preferably, the mixing in step (1) is carried out under the protection of dry inert gas; Preferably, the inert gas comprises nitrogen.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The conditions of the electrospinning in step (2) include: a voltage of 10 to 40 kV, a relative humidity of 40% to 60%, a distance from the Taylor cone to the receiving device for the meta-aramid nano nonwoven fabric of 5 to 30 cm, a spinning solution flow rate of 0.2 to 1 mL / h, and a hot air temperature of 40 to 80° C. In the meta-aramid nano nonwoven fabric obtained in step (2), the fiber diameter is 10 to 100 nm; The meta-aramid nano nonwoven fabric prepared in step (2) has an average thickness of 100 to 1000 nm, a porosity of 50% to 90%, a tensile strength of 0.05 to 0.9 MPa, and an elastic elongation of 4% to 18%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The conditions of the hot pressing in step (3) are as follows: the surface temperature of the hot pressing roller is 70-100° C., the working line pressure of the hot pressing is 1-50 kn / m, and the temperature of the hot air during the hot pressing process is 75-105° C.; Preferably, the drying conditions in step (3) are as follows: the surface temperature of the drying roller is 150-190°C; Preferably, the meta-aramid nano-slices in step (3) are square pieces with a side length of 4 to 10 mm; Preferably, the concentration of the liquid solvent to be recovered in step (2) and step (3) is both above 90%.
7. The preparation method according to any one of claims 1 to 6, characterized in that Adding desalted water during the slurry preparation in step (4); Preferably, the desalted water has a conductivity of <9 μs / cm, total Fe ≤ 50 μg / L, hardness ≤ 2 μmmol / L, and a pH value of 7 to 8; Preferably, the concentration of the slurry in step (4) is 1% to 5%; Preferably, the pulp inlet pressure during the pulping process in step (4) is 0.15-0.3 MPa; Preferably, the moisture content of the meta-aramid nano pulp in step (4) is 85% to 95%; Preferably, the specific surface area of the meta-aramid nano pulp in step (4) is 60 to 80 m 2 / g, length is 2-5mm; Preferably, the density of the meta-aramid nano pulp in step (4) is 1.33-1.36 g / cm 3 , the solvent content is less than 0.01%.
8. A preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises: (1) Preparation of meta-aramid spinning stock solution: Under the protection of dry inert gas, firstly, a poly(m-phenylene isophthalamide) solution with a concentration of 20% to 25% is added to a stock solution preparation tank, and then an amine solvent is added and stirred to obtain a meta-aramid spinning stock solution with a solid content of 8% to 18%; then, the meta-aramid spinning stock solution is cooled to 10 to 50° C.; (2) Preparation of meta-aramid nano nonwoven fabric: The meta-aramid spinning stock solution obtained in step (1) is conveyed to an electrospinning machine to obtain a meta-aramid nano nonwoven fabric having a fiber diameter of 10 to 100 nm, an average thickness of 100 to 1000 nm, a porosity of 50% to 90%, a tensile strength of 0.05 to 0.9 MPa, and an elastic elongation of 4% to 18%. During the preparation of the meta-aramid nano nonwoven fabric, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into a liquid, and then the liquid solvent is sent to a solvent recovery system; The conditions for electrospinning include: a voltage of 10 to 40 kV, a relative humidity of 40% to 60%, a distance from the Taylor cone to the receiving device for the meta-aramid nano nonwoven fabric of 5 to 30 cm, a spinning solution flow rate of 0.2 to 1 mL / h, and a hot air temperature of 40 to 80°C; (3) Preparation of meta-aramid nano-slices: The meta-aramid nano-nonwoven fabric obtained in step (2) is subjected to hot pressing, water washing and drying to complete the shaping of the meta-aramid nano-nonwoven fabric; the conditions for hot pressing and drying are: the surface temperature of the hot pressing roller is 70-100°C, the working line pressure of the hot pressing is 1-50 kn / m, the temperature of the hot air during the hot pressing process is 75-105°C, and the surface temperature of the drying roller is 150-190°C; the shaped meta-aramid nano-nonwoven fabric is then cut into square meta-aramid nano-slices with a side length of 4-10 mm by a slicer; during the hot pressing process, dry hot air is introduced to send the volatilized amine solvent into a heat exchanger to condense it into liquid, and then the liquid solvent is sent to a solvent recovery system; the washing water after washing is sent to a water treatment facility for processing and then reused; (4) Preparation of meta-aramid nano pulp: adding desalted water to the meta-aramid nano slices obtained in step (3) to prepare a slurry with a concentration of 1% to 5%, and then subjecting the pulp to the grinding, filtering and packaging steps to obtain the meta-aramid nano pulp; the filtrate after filtration is used as washing water in the washing section.
9. A meta-aramid nano pulp, characterized in that: The meta-aramid nano pulp is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the meta-aramid nano pulp according to claim 9 in aramid paper or reinforced composite materials.
Citation Information
Patent Citations
Method for preparing aromatic polyamide membrane type fibrid
CN104630924A
Precipitation apparatus
US3018091A
Synthetic paper structures of aromatic polyamides
US3756908A
Gas layer propulsion electrostatic spinning apparatus and industrial application thereof
CN101033559A
Anti-fuzzing m-aramid fiber paper with high mechanical strength
CN107354805A
Cited By
Aramid pulp with bionic plant branch fractal structure and preparation process thereof
CN119980750A